Oil product market outlook of Asia-Pacific and Vietnam to 2035 - Doan Tien Quyet; Tran Quoc Viet; Le Hoang Linh; Le Huyen Trang; Nguyen Thu Ha (Petrovietnam Journal, 2016)
The article introduces Wood Mackenzie’s forecast on demand and supply of oil products in the Asia-Pacific region and Vietnam to 2035. With an assumed GDP growth rate of 3.5% per annum, demand in the region is expected to reach 41.1 million b/d in 2035. In the supply side, with the existing 244 refineries (total refining capacity of around 34 million b/d), Asia-Pacific is forecast to increase its refining capacity to 2.1 million b/d from new refineries and the expansion of existing ones. Vietnam’s demand for oil products is forecast by Wood Mackenzie to continue to grow based on an estimated aver- age GDP growth of 4.4% per annum between 2015 and 2035, and reach 885,000 barrels per day in 2035.